Experimental and theoretical investigations of selenium graded cadmium telluride-based solar cells - Shah, Akash, author; Sampath, Walajabad S., advisor; Weinberger, Chris, advisor; Sites, James, committee member; Martinez, Umberto, committee member (Colorado State University. Libraries, 2022)
In the past few years, cadmium telluride (CdTe) based solar cells have emerged as an important photovoltaic (PV) technology for electricity generation. The optimal bandgap of the absorber material and high throughput manufacturing methods make CdTe PV a leading cost-competitive alternative to silicon solar cells. However, the performance of CdTe PV-devices strongly depends on the processing of the absorber layer. This work uses experiments in conjunction with two-probe atomistic models based on density functional theory (DFT) to understand the processing effects on the electronic properties of heterostructures in CdTe PV-devices and improve the efficiencies of CdTe solar cells. Various processing conditions such as cadmium chloride (CdCl2) treatment and selenium (Se) alloying of CdTe absorber layer were found to improve the PV-device efficiencies (from 0.22% to 18.3%). Atomistic simulation models utilized DFT coupled with Green's function to investigate the electronic properties of thin film surfaces, grain boundaries and interfaces within theCdSeTe/CdTe PV-device configuration. Structural and electronic properties of bulk CdSexTe1-x and CdSe0.25Te0.75 surfaces were calculated and compared with the experimental and theoretical literature to establish the modeling parameters. The results from the elemental characterization done on the CdCl2 treated CdSeTe/CdTe films formed the basis of respective CdSeTe/CdTe interface and grain-boundary atomistic models. The electronic properties calculated for Se-graded CdSeTe/CdTe interfaces showed a pick up in the conduction band (CB) energy level (creating electron reflector effect) and was verified experimentally by Ultraviolet Photoelectron Spectroscopy (UPS). DFT models also suggested that higher p-doping is required in CdSeTe-only absorber to achieve similar electron reflector effect at the CdSeTe/Te interface. The grain-boundary models further showed that presence of Se and Cl at the CdTe grain-boundary passivates the critical acceptor defect states and leads to n-type inversion at the grain-boundary. The band engineering and defect state passivation in the Cl and Se-alloyed CdTe solar cells efficiently extracted the charge carriers, thereby producing high-performing CdSeTe/CdTe PV-devices ( 19.4%). In comparison to unalloyed CdTe absorbers, Se alloying passivated the defect states in CdTe grain boundaries. It has also been observed that Alumina/CdSeTe/Alumina double heterostructures showed higher minority carrier lifetime indicating better passivation in the bulk and the oxide/absorber interface. The electronic properties calculated via DFT suggested Te/O interface formation at the CdSeTe/Alumina interface led to reduction in the interfacial defect states. This combination of lower density of defect states at the CdSeTe grain boundaries and CdSeTe/oxide interface produces high lifetime (430 ns) in the oxide/CdSeTe double heterostructures. Following this, TeOx was also used as the back passivation layer of unalloyed CdSeTe/CdTe bilayer to produce 19% efficient CdTe PV-devices. The introduction of TeOx as the potential passivation layer eliminates the requirement of copper doping in the CdTe PV-devices, thereby increasing the longevity of CdTe solar panels in the field.
Keywords: CdSeTe grain boundary; density functional theory; atomistic modeling; interfaces; CdTe solar cells